Development of technology of obtaining microcrystalline cellulose from flax fibres - Барбаш, Валерій Анатолійович; Нагорна, Юлія Миколаївна (Eastern-European Journal of Enterprise Technologies, 2015)
The process of obtaining microcrystalline cellulose from flax fibers was investigated. The effect of chelating agents on the mineral content in the flax cellulose was studied. The influence of the elemental composition of flax cellulose on the content of metal cations after chelating treatment was determined. It was found that metal cations are the most extractable in alkaline and acidic media at pH=3 and pH=12. The process of bleaching flax cellulose that does not contain hazardous chlorine compounds was investigated and optimal bleaching scheme, that allows to achieve the required whiteness at low content of non-cellulose components, including minerals, was found. The main technical parameters of the bleached flax cellulose hydrolysis were determined. For the production of microcrystalline cellulose from flax fibers, it is recommended to use the following scheme for processing flax fibers: soda pulping – bleaching according to the scheme with chelating treatment in an acidic medium – two-stage peroxide bleaching – hydrolysis. Using the proposed scheme allows to obtain microcrystalline cellulose that meets regulatory requirements and can be used in the chemical industry.